Surface water-groundwater interactions and local land use control water quality impacts of extreme rainfall and flooding in a vulnerable semi-arid region of Sub-Saharan Africa - Geris, J.; Comte, J.-C.; Franchi, F.; Petros, A. K.; Tirivarombo, S.; Selepeng, A. T.; Villholth, Karen G. (Elsevier, 2022)
While extreme rainfall events may provide rare opportunities for replenishment of surface water and groundwater resources in vulnerable (semi)arid areas, they are typically also associated with widespread flooding. The impacts on contaminant movement associated with spatio-temporally complex relationships between surface water and groundwater during such events in these regions are largely unknown. The catchment area (~4350 km2) upstream of Gaborone Dam on the Notwane River in south-east Botswana and northern South Africa experienced extreme rainfall and major flooding in 2016/17, following a severe 5-year drought. In this generally data-sparce area, we collected a unique data set that combined traditional water quantity observations with stable water isotope, major ion, trace metal and geophysical data. These were analysed to gain insights into water quantity and quality dynamics following flooding, including contaminant movement using trace metals as pollution indicators. Results revealed that the extreme rainfall and flooding was responsible for replenishment of surface water and groundwater resources, but also contaminant mobilisation from the surface. This subsequently resulted in increased concentrations of contaminants during the recession. Overall, hydrogeological heterogeneity dictated spatially variable surface water - groundwater interactions, characterised by poor connectivity in low productivity aquifer areas as opposed to good connectivity in moderate to high productivity aquifers. This in turn affected water quality dynamics and contamination, locally superimposed by land use impacts, primarily from urban landfill and local agricultural practices. Groundwater-connected streams had consistently lower (responses in) contaminants. We also found that Gaborone Reservoir facilitated prolonged conditions for recharge but likely also enhanced contamination of groundwater through maintaining a high water table in urban areas located immediately downstream. Management implications of our findings include a requirement for careful consideration of land use and landfill planning in relation to bedrock geology and presence of surface water reservoirs, conjunctive surface water and groundwater management, but also the need for even higher (space-time) resolution of monitoring in these data sparce environments. This could contribute to enhancing the benefits that extreme rainfall events provide in terms of surface water and groundwater resources replenishment for future dry seasons and periods of drought.